Coexistence of pressure-induced structural phases in bulk black phosphorus: a combined x-ray diffraction and Raman study up to 18 GPa. (19th November 2018) - Joseph, B; Caramazza, S; Capitani, F; Clarté, T; Ripanti, F; Lotti, P; Lausi, A; Di Castro, D; Postorino, P; Dore, P
Abstract: We report a study of the structural phase transitions induced by pressure in bulk black phosphorus by using both synchrotron x-ray diffraction for pressures up to 12.2 GPa and Raman spectroscopy up to 18.2 GPa. Very recently black phosphorus attracted large attention because of the unique properties of few-layers samples (phosphorene), but some basic questions are still open in the case of the bulk system. As concerning the presence of a Raman spectrum above 10 GPa, which should not be observed in an elemental simple cubic system, we propose a new explanation by attributing a key role to the non-hydrostatic conditions occurring in Raman experiments. Finally, a combined analysis of Raman and XRD data allowed us to obtain quantitative information on presence and extent of coexistences between different structural phases from ~5 up to ~15 GPa. This information can have an important role in theoretical studies on pressure-induced structural and electronic phase transitions in black phosphorus.